Evaluation of a Model for Efficient Screening of Tuberculosis Contact Subjects - Aissa, Khaoula; Madhi, Fouad; Ronsin, Nathalie; Delarocque, France; Lecuyer, Aurelie; Decludt, Benedicte; Remus, Natacha; Abel, Laurent; Poirier, Christine; Delacourt, Christophe; CG94 Study Group (American journal of respiratory and critical care medicine, 2008)
Contact tracing is an important component of tuberculosis (TB) control programs. Standardization of contact investigation protocols can make them more efficient. To develop a model to select contact subjects for screening. We prospectively collected standardized data on 325 TB index cases and their 2,009 contacts. Factors that independently influenced the risk of TB infection were included in the model, which was then validated in a second prospective cohort of 88 cases of TB and their 618 contacts. A total of eight independent risk factors were identified (odds ratio; 95% confidence interval): age, with three subgroups: 6-14 years (3.6; 1.6-8.0); 15-29 years (3.7; 1.8-7.7); > or =30 years (4.1; 2.0-8.5); cavitation on the index case's chest radiograph (1.6; 1.1-2.2); an index case sputum smear with 100 or more acid-fast bacilli per field (1.8; 1.2-2.8); household contact at night (2.1; 1.3-3.2); first-degree family relationship with the index case (2.1; 1.3-3.3); active smoking by the contact (1.6; 1.1-2.4); free health care (2.0; 1.2-3.2); and birth in a country with TB incidence rate higher than 25 of 100,000 (2.2; 1.5-3.2). Predictive probabilities were chosen to ensure false-negative rates lower than estimated TB infection background. The number of contacts to be investigated was reduced by 26% while maintaining a false-negative rate of 8%. This study provides a standardized contact screening model which reduces resources required without negatively affecting disease control.